STUDI KOMPARATIF TENTANG PERAN DAN KEDUDUKAN MAJELIS PERMUSYAWARATAN RAKYAT MASA ORDE BARU DAN MASA REFORMASI 1999 (Lex Jurnalica, 2019)
AbstractThe purpose of this research is, first, to determine the position and role of the Assembly in the New Order and the Reform Era. Second, explore various constitutional practices that are relevant to the position and role of the Assembly in the New Order and the Reform Era.The research process is done through literature research and study, any data used is secondary data. Furthermore, the data were analyzed using qualitative approach adapted to the formulation of the problems in this study and is based on a theoretical framework that has been compiled. The analysis process is done by first classifying the data through an inventory of the various provisions of the 1945 Constitution and other legislation relating to the status and role of the Assembly, in which then historically compared with data and theories that relevant to the subject. The next step is put data in a systematic order that has been classified, which becamethe. basis of the conclusions and suggestions.The results of this study indicate, first, under Article 1 Paragraph (2) of the 1945 Constitution, the Assembly serves as the highest state institution in the New Order with the various authorities as provided in Article 3, Article 6 Paragraph (2), Article 9 and Article 37 of the 1945 Constitution. Nevertheless, the Assembly cannot play the role of implementing the people's sovereignty as a result of the President's authority to appoint the majority members of the Assembly so that it affects the institutional independence. Second, the reform event has encouraged series of shifting in the position and role of the Assembly. Based on an amendment to Article 2 Paragraph (1) of the 1945 Constitution, the Assembly no longer serves as the highest state institution. The role of the Assembly was no longer as the executor of the people's sovereignty. Despite the decline in the position, the role of the Assembly increased proportionally to the scope of authority and the new position. Third, the basic problem of weakening the role of the Assembly in the New Order is not only derived from the 1945 Constitution’s internal boundaries, but also deviation of constitutional practice in the New Order. Keyword: comparative, position, roleAbstrakTujuan penilitian ini adalah, pertama, untuk mengetahui dan menganalisis kedudukan dan peran MPR pada masa Orde Baru dan Reformasi. Kedua, menelusuri berbagai praktik ketatanegaraan yang relevan terhadap kedudukan dan peran MPR pada masa Orde Baru dan Reformasi. Jenis penelitian ini adalah yuridis normatif. Proses penelitian dilakukan melalui penelitian kepustakaan atau studi literatur, data yang dipergunakan pun adalah data sekunder. Selanjutnya, data hasil penelitian dianalisis menggunakan pendekatan kualititatif disesuaikan dengan rumusan permasalahan dalam penelitian ini dan didasarkan pada kerangka teori yang telah disusun. Proses analisis dilakukan dengan terlebih dahulu mengklasifikasikan data melalui inventarisasi berbagai ketentuan dalam UUD 1945 dan peraturan perundang-undangan lain yang berkaitan dengan kedudukan dan peran MPR serta selanjutnya dikomparasikan dengan data historis dan teori yang relevan dengan objek yang diteliti. Langkah berikutnya adalah mensistematisasi data yang telah terklasifikasi. Hasil penelitian ini menunjukkan: Pertama, berdasarkan Pasal 1 ayat (2) UUD 1945, pada masa Orde Baru MPR berkedudukan sebagai lembaga tertinggi negara. Kendati demikian, MPR tidak dapat memainkan peranan pelaksana kedaulatan rakyat akibat kewenangan Presiden mengangkat sebagian anggota MPR sehingga berpengaruh pada independensi kelembagaan. Kedua, pada Reformasi tahun 1999 meski kedudukan MPR secara konstitusional belum berubah, MPR lebih mampu menjalankan perannya. Hal itu dikarenakan oleh perubahan sistem kepartaian menjadi multi partai dan sistem pemilu yang lebih terbuka. Kata kunci: Komparasi, kedudukan, peran